PRODUKSI BIODIESEL DARI CPO DENGAN PROSES ESTERIFIKASI DENGAN KATALIS H2SO4 DAN TRANSESTERIFIKASI DENGAN KATALIS CaO DARI CANGKANG KERANG DARAH - Tengku Ryhaan Permata Sari Devi; Nurhayati '; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Biodiesel is one of alternative fuel to replace diesel that was derived from petroleum. The objective of this research is to optimize biodiesel production from CPO raw material through esterification reaction catalyzed with H2SO4 and transesterification catalyzed with CaO originally from blood cockle. The esterification reaction was carried out with the weight variation of the catalyst and mol ratio of oil to methanol. Before performing biodiesel synthesis the water content and free fatty acid (FFA) were determined. Water content obtained was 0,4% and FFA was 5,0187%. The maximum biodiesel produced was 77,93% that was obtained from reaction by 2%wt H2SO4 catalyst with mol ratio of oil to methanol 1:24.